Effect of season on sun drying of cocoa beans in Brazil - Ghosh, B.N.; Cunha, J. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
Natural or sun-drying of cocoa beans in Brazil, after fermentation, takes place on a flat, smooth, horizontal platform called a "barcaca." This paper presents the results of an experimental study conducted at the Centro de Pesquisas do Cacau in Brazil to study the effect of season and various climatic factors on the drying rate of cocoa beans. It takes an average of 10 days to sun-dry a load of beans, with minimum and maximum recorded values ​​of 5 and 12 days, respectively. However, it is known that under adverse conditions, up to 20 to 22 days may be required. 84 percent moisture extraction from the beans is required to produce a dry sample. An average of 55 hours of sunlight and 65 hours of open barcaca are required to dry a load.